The Implementation of Active Learning Methods to Improve Early Childhood Students' Ability to Memorize Daily Prayers at RA Plus Ja-Alhaq, Bengkulu City - Nadia Fanisa; Irwan Satria; Ahmad Syarifin (The Future of Education Journal, 2026)
The ability to memorize daily prayers in early childhood is an important aspect in developing religious and moral values. However, during the learning process, children are still found to be less active and not optimal in memorizing daily prayers. This study aims to determine the application of active learning methods, the responses of early childhood children, and the supporting and inhibiting factors in improving the ability to memorize daily prayers in early childhood at RA Plus Ja-Alhaq in Bengkulu City. The research method used was qualitative with a descriptive approach. The subjects consisted of teachers and early childhood children. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion drawing. The results showed that the application of active learning methods in memorizing daily prayers was carried out in a planned and systematic manner through prayer repetition, hand movements, singing, and the use of learning media. Teachers also actively invited, guided, and provided stimulation to children to repeat memorization, both collectively and individually, so that children were more motivated and engaged in the learning process. Children's responses tended to be positive, characterized by enthusiasm, activeness, and enjoyment in participating in the learning process. Supporting factors included the role of teachers, the use of engaging media, and collaboration with parents. Inhibiting factors include differences in children's abilities, concentration levels, and lack of repetition at home. The research concluded that active learning methods are effective in improving daily prayer memorization skills in early childhood and can create a fun and meaningful learning environment.